Now & again ebook Go-to recipes, inspired menus + endless ideas for reinventing leftovers. - Turshen, Julia (2018)
Small Victories, one of the most beloved cookbooks of 2016, introduced us to the lovely Julia Turshen and her mastery of show-stopping home cooking, and her second book, Feed the Resistance, moved a nation, winning Eater Cookbook of the Year in 2017. In Now & Again, the follow-up to what Real Simple called "an inspiring addition to any kitchen bookshelf," more than 125 delicious and doable recipes and 20 creative menu ideas help cooks of any skill level to gather friends and family around the table to share a meal (or many!) together. This cookbook comes to life with Julia's funny and encouraging voice and is brimming with good stuff, including: can't-get-enough-of-it recipes inspiring menus for social gatherings, holidays and more helpful timelines for flawlessly throwing a party oh-so-helpful "It's Me Again" recipes, which show how to use leftovers in new and delicious ways tips on how to be smartly thrifty with food choices Now & Again will change the way we gather, eat, and think about leftovers, and, like the name suggests, you'll find yourself reaching for it time and time again.